Primaquine-quinoxaline 1,4-di-N-oxide hybrids with action on the exo-erythrocytic forms of Plasmodium induce their effect by the production of reactive oxygen species (2019)
ABSTRACT: Background: The challenge in anti-malarial chemotherapy is based on the emergence of resistance to drugs and the search for medicines against all stages of the life cycle of Plasmodium spp. as a therapeutic target. Nowadays, many molecules with anti-malarial activity are reported. However, few studies about the cellular and molecular mechanisms to understand their mode of action have been explored. Recently, new primaquine-based hybrids as new molecules with potential multi-acting anti-malarial activity were reported and two hybrids of primaquine linked to quinoxaline 1,4-di-N-oxide (PQ-QdNO) were identified as the most active against erythrocytic, exoerythrocytic and sporogonic stages. Methods: To further understand the anti-malarial mode of action (MA) of these hybrids, hepg2-CD81 were infected with Plasmodium yoelii 17XNL and treated with PQ-QdNO hybrids during 48 h. After were evaluated the production of ROS, the mitochondrial depolarization, the total glutathione content, the DNA damage and proteins related to oxidative stress and death cell. Results: In a preliminary analysis as tissue schizonticidals, these hybrids showed a mode of action dependent on peroxides production, but independent of the activation of transcription factor p53, mitochondrial depolarization and arrest cell cycle. Conclusions: Primaquine-quinoxaline 1,4-di-N-oxide hybrids exert their antiplasmodial activity in the exoerythrocytic phase by generating high levels of oxidative stress which promotes the increase of total glutathione levels, through oxidation stress sensor protein DJ-1. In addition, the role of HIF1a in the mode of action of quinoxaline 1,4-di-N-oxide is independent of biological activity. Keywords: 4-Di-N-oxide; Cell death; Exoerythrocytic stage; Malaria; Oxidative stress; Plasmodium; Quinoxaline 1.